Costunolide Inhibits Chronic Kidney Disease Development by Attenuating IKKβ/NF-κB Pathway - Zhao Y; Wang YH; Tu WC; Wang DW; Lu MJ; Shao Y (Dove Medical Press, 2024)
Yang Zhao,1,* Yi-Han Wang,2,* Wei-Chao Tu,1 Da-Wei Wang,1 Mu-Jun Lu,3,4 Yuan Shao1 1Department of Urology, Ruijin Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, Shanghai, 201800, People's Republic of China; 2Department of Urology, Sixth People's Hospital South Campus Affiliated to Shanghai Jiao Tong University, Shanghai, People's Republic of China; 3Department of Urology and Andrology, Renji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People's Republic of China; 4Shanghai Institute of Andrology, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Mu-Jun Lu; Yuan Shao, Email lumujun@163.com; shaoyuan10772@163.comBackground: Chronic kidney disease (CKD) is a significant worldwide health concern that leads to high mortality rates. The bioactive substance costunolide (CTD) has demonstrated several pharmacological effects and holds promise as a CKD treatment. This study aims to investigate the impact of CTD on CKD and delve into its mechanisms of action.Methods: Unilateral ureteral obstruction (UUO) methods and renal fibrosis mice models were created. Various concentrations of CTD were injected into UUO mice models to investigate the therapeutic effects of CTD on renal fibrosis of mice. Then, renal morphology, pathological changes, and the expression of genes related to fibrosis, inflammation and ferroptosis were analysed. RNA sequencing was utilized to identify the main biological processes and pathways involved in renal injury. Finally, both overexpression and inhibition of IKKβ were studied to examine their respective effects on fibrosis and inflammation in both in vitro and in vivo models.Results: CTD treatment was found to significantly alleviate fibrosis, inflammation and ferroptosis in UUO-induced renal fibrosis mice models. The results of RNA sequencing suggested that the IKKβ acted as key regulatory factor in renal injury and the expression of IKKβ was increased in vitro and in vivo renal fibrosis model. Functionally, down-regulated IKKβ expression inhibits ferroptosis, inflammatory cytokine production and collagen deposition. Conversely, IKKβ overexpression exacerbates progressive renal fibrosis. Mechanistically, CTD alleviated renal fibrosis and inflammation by inhibiting the expression of IKKβ and attenuating IKKβ/NF-κB pathway.Conclusion: This study demonstrates that CTD could mitigate renal fibrosis, ferroptosis and inflammation in CKD by modulating the IKKβ/NF-κB pathway, which indicates targeting IKKβ has an enormous potential for treating CKD. Keywords: chronic kidney disease, costunolide, renal fibrosis, IKKβ/NF-κB pathway